Tìm x :
1) \(x^2-4=0\) 7) \(x^2-14x+13=0\)
2) \(2x^2-8=0\) 8) \(x^2+10x+16=0\)
3) \(\left(x+3\right)^2=4\)
4) \(\left(x-7\right)^2=36\)
5) \(x^2-14x=-49\)
6) \(x^2+6x+5=0\)
1) x2 - 4 = 0
=> x2 = 4
=> x = \(\pm\)2
2) 2x2 - 8 = 0
=> 2x2 = 8
=> x2 = 4
=> x = \(\pm2\)
3) (x + 3)2 = 4 => (x + 3)2 = 22
=> \(\orbr{\begin{cases}x+3=2\\x+3=-2\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=-5\end{cases}}\)
4) (x - 7)2 = 36
=> (x - 7)2 = 62
=> \(\orbr{\begin{cases}x-7=6\\x-7=-6\end{cases}}\Rightarrow\orbr{\begin{cases}x=13\\x=1\end{cases}}\)
5) x2 - 14x = -49
=> x2 - 14x + 49 = 0
=> x2 - 7x - 7x + 49 = 0
=> x(x - 7) - 7(x - 7) = 0
=> (x - 7)2 = 0
=> x = 7
6) x2 + 6x + 5 = 0
=> x2 + x + 5x + 5 = 0
=> x(x + 1) + 5(x + 1) = 0
=> (x + 1)(x + 5) = 0
=> \(\orbr{\begin{cases}x=-1\\x=-5\end{cases}}\)
7) x2 - 14x + 13 = 0
=> x2 - x - 13x + 13 = 0
=> x(x - 1) - 13(x - 1) = 0
=> (x - 1)(x - 13) = 0
=> \(\orbr{\begin{cases}x=1\\x=13\end{cases}}\)
8) x2 + 10x +16 = 0
=> x2 + 2x + 8x + 16 = 0
=> x(x + 2) + 8(x + 2) = 0
=> (x + 2)(x + 8) = 0
=> \(\orbr{\begin{cases}x=-2\\x=-8\end{cases}}\)